Understanding the lived experiences of ambulant vendos towards establishing a formal business system for sustainability in Tacloban City - Blando, Jullianne Marie B.; Corillo, Jomar T.; Globio, Diana Rose D.
This study delves into the lives of ambulant vendors in downtown Tacloban City, examining their business practices, challenges and coping strategies, to understand their significance and why they choose to stay informal despite the many benefits that formalization offers. The fundamental objective of the study is to utilize these understandings in providing avenues of opportunities for policymakers to craft policies that would foster sustainable economic growth among these vendors. Using qualitative phenomenology, the researchers conducted in-depth interviews with 14 participants identified using a purposive sampling technique and applied Colaizzi's methodological approach for analysis. Findings revealed that their challenges center around regulatory restrictions and vulnerability to weather conditions, which they counter and adapt by establishing informal networks or social organizations and complying with city policies to avoid conflicts. These factors influence their perceptions of formalization, with many expressing reservations due to perceived barriers like financial constraints or lack of knowledge in the process and benefits of registration. However, they continue to express aspirations to formalize generally for long-term sustainability. Their needs and expectations are concentrated on accessible permanent locations, inexpensive registration and maintenance expenses, or similar programs as government subsidies. The findings of this study offer significant insights for the city government on how they can create potential interventions for these businesses such as strengthening regulatory policies by including educational programs regarding business licensing and operations for ambulant vendors to encourage them to transition into a formal business structure.